São Paulo urban heat islands have a higher incidence of dengue than other urban areas - Ricardo Vieira Araujo; Marcos Roberto Albertini; André Luis Costa-da-Silva; Lincoln Suesdek; Nathália Cristina Soares Franceschi; Nancy Marçal Bastos; Gizelda Katz; Vivian Ailt Cardoso; Bronislawa Ciotek Castro; Margareth Lara Capurro; Vera Lúcia Anacleto Cardoso Allegro (Brazilian Journal of Infectious Diseases, 2015)
Urban heat islands are characterized by high land surface temperature, low humidity, and poor vegetation, and considered to favor the transmission of the mosquito-borne dengue fever that is transmitted by the Aedes aegypti mosquito. We analyzed the recorded dengue incidence in Sao Paulo city, Brazil, in 2010–2011, in terms of multiple environmental and socioeconomic variables. Geographical information systems, thermal remote sensing images, and census data were used to classify city areas according to land surface temperature, vegetation cover, population density, socioeconomic status, and housing standards. Of the 7415 dengue cases, a majority (93.1%) mapped to areas with land surface temperature >28 °C. The dengue incidence rate (cases per 100,000 inhabitants) was low (3.2 cases) in high vegetation cover areas, but high (72.3 cases) in low vegetation cover areas where the land surface temperature was 29 ± 2 °C. Interestingly, a multiple cluster analysis phenogram showed more dengue cases clustered in areas of land surface temperature >32 °C, than in areas characterized as low socioeconomic zones, high population density areas, or slum-like areas. In laboratory experiments, A. aegypti mosquito larval development, blood feeding, and oviposition associated positively with temperatures of 28–32 °C, indicating these temperatures to be favorable for dengue transmission. Thus, among all the variables studied, dengue incidence was most affected by the temperature. Keywords: Urban heat islands, Land surface temperature, Vegetation cover, Dengue, Aedes aegypti